RNA Sequencing and Pathways Analyses of Middle Ear Epithelia From Patients With Otitis Media. (12th April 2021) - Stabenau, Kaleigh A.; Zimmermann, Michael T.; Mathison, Angela; Zeighami, Atefeh; Samuels, Tina L.; Chun, Robert H.; Papsin, Blake C.; McCormick, Michael E.; Johnston, Nikki; Kerschner, Joseph E.
Abstract : Objectives: Otitis media (OM) is the most common pediatric diagnosis in the United States. However, our understanding of the molecular pathogenesis of OM remains relatively poor. Investigation of molecular pathways involved in OM may improve the understanding of this disease process and elucidate novel therapeutic targets. In this study, RNA sequencing (RNA‐Seq) was used to discern cellular changes associated with OME compared to healthy middle ear epithelium (MEE). Study Design: Ex vivo case‐control translational. Methods: Middle ear epithelia was collected from five pediatric patients diagnosed with OME undergoing tympanostomy tube placement and five otherwise healthy pediatric patients undergoing cochlear implantation. Specimens underwent RNA‐Seq and pathways analyses. Results: A total of 1, 292 genes exhibited differential expression in MEE from OME patients compared to controls including genes involved in inflammation, immune response to bacterial OM pathogens, mucociliary clearance, regulation of proliferation and transformation, and auditory cell differentiation. Top networks identified in OME were organismal injury and abnormalities, cell morphology, and auditory disease. Top Ingenuity canonical pathways identified were axonal guidance signaling, which contains genes associated with auditory development and disease and nicotine degradation II and III pathways. Associated upstream regulators included β‐estradiol, dexamethasone, and G‐protein‐coupled estrogen receptor‐1 (GPER1), which are associated with otoprotection or inflammation during insult. Conclusions: RNA‐Seq demonstrates differential gene expression in MEE from patients with OME compared to healthy controls with important implications for infection susceptibility, hearing loss, and a role for tobacco exposure in the development and/or severity of OME in pediatric patients. Level of Evidence: 4 Laryngoscope, 131:2590–2597, 2021